Eco-friendly green synthesis of dextrin based poly (methyl methacrylate) grafted silver nanocomposites and their antibacterial and antibiofilm efficacy against multi-drug resistance pathogens. (1st September 2019) - Hasan, Imran; Qais, Faizan Abul; Husain, Fohad Mabood; Khan, Rais Ahmad; Alsalme, Ali; Alenazi, Bader; Usman, Mohammad; Jaafar, Mohammed H.; Ahmad, Iqbal
Abstract: Multi-drug resistance (MDR) poses a serious threat in the management of infectious diseases. Slow development of antibiotics and acquirement of resistance mechanisms has led the researchers to focus on development of novel chemotherapeutic agents with broad-spectrum activity having multiple sites of action. Till date, nanoparticles are proven to be a good alternative in management of MDR at least under laboratory conditions. In this study, dextrin was used for eco-friendly green synthesis of silver nanoparticles grafted by poly (methyl methacrylate). The nanoparticles were characterized using UV–vis spectroscopy, FTIR, XRD, SEM, EDX and TEM. The synthesized nanoparticles (PMMA-g-Dex@Ag) were then evaluated for antimicrobial and antibiofilm efficacy on multi-drug resistance bacterial and fungal pathogens. PMMA-g-Dex@Ag proved to be good bacteriostatic even at 4 μg/ml. The minimum inhibitory concentration (MIC) against C. albicans was found to be 16 μg/ml. Moreover, the biofilms of all tested pathogens were reduced by approximately more than 70% in presence of highest tested sub-MIC. Inhibition of exopolysaccharides (EPS) secretion supported the biofilms data and deciphered a possible mode of action. Therefore, such green synthesized nanoparticles can be used as an alternative in management of MDR infection at least for tropical application after careful in vivo validation. Graphical abstract: Image 1 Highlights: An eco-friendly nanocomposite has been synthesised using dextrin. The nanocomposites were antibacterial at remarkably low concentration. The nanocomposites proved to possess potent antibiofilm activity. The nanocomposites showed broad-spectrum antibiofilm activity.